PENGARUH KESEJAHTERAAN DAN DESAIN PEKERJAAN TERHADAP KEPUASAN KERJA PADA PT. PERKEBUNAN NUSANTERA III (PERSERO) PKS TORGAMBA KABUPATEN LABUHANBATU SELATAN - Hasibuan, Desmawaty; Martho Hendry, Raja Saul (LPPM Universitas Labuhanbatu, 2020)
This study aims to analyze the effect of welfare and job design on employee job satisfaction at PT.Perkebunan Nusantara III (Persero) PKS Torgamba, Labuhanbatu Selatan Regency. The data collection methods in this study are questionnaires, interviews, documentation and observation. The sampling technique used is probability sampling technique. The population which is the object of this research is the employees of PT. Perkebunan Nusantara III (Persero) PKS Torgamba, South Labuhanbatu Regency, totaling 55 people. Hypothesis testing is done by multiple linear regression analysis through the SPSS 20.0 for windows program. Based on the results of the study with a significance level of 5%, the conclusion is that the tcount for the Welfare variable is 5.733, the worker design is 5.926. Based on the criteria that if the value of tcount> ttable); namely (5,733> 1,674, (5,926> 1,674) so it can be concluded that partially the Welfare variable has a positive and significant effect on Job Satisfaction, Employee Design has a positive and significant effect on Job Satisfaction of Employees of PT Perkebunan Nusantara III (Persero) PKS Torgamba, South Labuhanbatu Regency.